A cluster-randomized, non-inferiority trial comparing use of misoprostol for universal prophylaxis vs. secondary prevention of postpartum hemorrhage among community level births in Egypt - Holly A. Anger; Rasha Dabash; Nevine Hassanein; Emad Darwish; Mohamed Cherine Ramadan; Medhat Nawar; Dyanna Charles; Miral Breebaart; Beverly Winikoff (BMC, 2020)
Abstract Background Previous community-based research shows that secondary prevention of postpartum hemorrhage (PPH) with misoprostol only given to women with above-average measured blood loss produces similar clinical outcomes compared to routine administration of misoprostol for prevention of PPH. Given the difficulty of routinely measuring blood loss for all deliveries, more operational models of secondary prevention are needed. Methods This cluster-randomized, non-inferiority trial included women giving birth with nurse-midwives at home or in Primary Health Units (PHUs) in rural Egypt. Two PPH management approaches were compared: 1) 600mcg oral misoprostol given to all women after delivery (i.e. primary prevention, current standard of care); 2) 800mcg sublingual misoprostol given only to women with 350-500 ml postpartum blood loss estimated using an underpad (i.e. secondary prevention). The primary outcome was mean change in pre- and post-delivery hemoglobin. Secondary outcomes included hemoglobin ≥2 g/dL and other PPH interventions. Results Misoprostol was administered after delivery to 100% (1555/1555) and 10.7% (117/1099) of women in primary and secondary prevention clusters, respectively. The mean drop in pre- to post-delivery hemoglobin was 0.37 (SD: 0.91) and 0.45 (SD: 0.76) among women in primary and secondary prevention clusters, respectively (difference adjusted for clustering = 0.01, one-sided 95% CI: < 0.27, p = 0.535). There were no statistically significant differences in secondary outcomes, including hemoglobin drop ≥2 g/dL, PPH diagnosis, transfer to higher level, or other interventions. Conclusions Misoprostol for secondary prevention of PPH is comparable to universal prophylaxis and can be implemented using local materials, such as underpads. Trial registration Clinicaltrials.gov NCT02226588 , date of registration 27 August 2014.